2018
DOI: 10.1177/0018726718761553
|View full text |Cite
|
Sign up to set email alerts
|

Who will I be when I retire? Introducing a Lacanian typology at the intersection of present identity work and future narratives of the retired self

Abstract: The study introduces a framework by which insights from Lacanian psychoanalysis can be employed to offer a more nuanced understanding of how retirement is currently being reinvented. Building on an analysis of 49 stories in which early-career employees describe their retirement aspirations, the study explores the complexities of how individuals draw on retirement discourse to articulate who they are and what they want. The analysis suggests that the narrative construction of retirement is not only a space for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 55 publications
(148 reference statements)
0
22
0
1
Order By: Relevance
“…In the context of process thinking, then, we might understand organization as the collective sedimentation of interacting patterns of immediate action (experiment, intuition, curiosity, reaction) and extended reflection (routines, standards, expectations). As such organization itself becomes a temporal phenomenon whose forms are the residue of continually adjusting configurations of immediate experience made possible by the admission of information cast as the future (expectation) and the past (memory), as, for example, in Driver’s (2018) compelling study of how retirement discourse can encapsulate a struggle for articulating oneself in the present.…”
Section: Time-for-us Iii: the Process-oriented Viewmentioning
confidence: 99%
“…In the context of process thinking, then, we might understand organization as the collective sedimentation of interacting patterns of immediate action (experiment, intuition, curiosity, reaction) and extended reflection (routines, standards, expectations). As such organization itself becomes a temporal phenomenon whose forms are the residue of continually adjusting configurations of immediate experience made possible by the admission of information cast as the future (expectation) and the past (memory), as, for example, in Driver’s (2018) compelling study of how retirement discourse can encapsulate a struggle for articulating oneself in the present.…”
Section: Time-for-us Iii: the Process-oriented Viewmentioning
confidence: 99%
“…In contrast, Whiting and Pritchard (2018), examined 'the weary', a label coined to refer to working entrepreneurial and active retirees, highlighting the destabilisation of retirement and its discursive re-conceptualisation as a period of entrepreneurial endeavour. Driver (2017) highlighted the critical importance of being active and purposeful and remaining an attractive labour commodity. She suggested that, through work, older individuals can avoid financial insecurity and physical decline, and resultant loss of status and social marginalisation, avoid experiencing boredom and loss of purpose, and so live a happier and healthier life.…”
Section: Reasons To Retire/ Continue To Workmentioning
confidence: 99%
“…The psychodynamic tradition enables understanding of such unconscious facets of identity and is a useful supplement to the discursive identity tradition. Within the psychodynamic tradition, facets of Lacan's extensive corpus of work (e.g., Lacan & Fink, 2002), and, particularly, Driver's (2009aDriver's ( , 2009bDriver's ( , 2017Driver's ( , 2018 interpretations of Lacan's work, provide a basis for understanding mentoring relationships in terms of identity-work.…”
Section: Mentoring Identity-work and The Unconsciousmentioning
confidence: 99%
“…Through identity-work, people “create, adapt, signify, claim and reject identities from available resources” (Brown, 2017, p. 298) and attempt to “influence the various social identities which pertain to them” (Watson, 2009, p. 431) in attempting to secure a degree of “existential continuity and security” (Alvesson & Willmott, 2002, p. 622). Given the precarity of identities, identity-work is continually needed and is typically seen as a perpetual struggle (Clarke et al, 2009; Driver, 2018). A considerable literature has emerged demonstrating the utility of identity-work in understanding a broad range of individual and organizational phenomena, and in a recent comprehensive review of the identity-work literature, Brown (2017) discerned five distinct approaches to understanding identity-work (see also Caza et al, 2018).…”
Section: Mentoring Enabling Protégés’ Identity-workmentioning
confidence: 99%
See 1 more Smart Citation